Pengaruh Debt Tax Shield dan Efektif Tax Rate Terhadap Struktur Modal Pada Perusahaan Advertising Printing Media - Haervi Yunira (Politeknik Ganesha Medan, 2022)
Capital structure is the ratio between debt and equity. Capital structure is useful for measuring the proportion of debt and equity used as a source of company funding. This study aims to examine the Debt tax shield, and the Effective Tax Rate on the capital structure of Advertising Printing Media companies listed on the Indonesia Stock Exchange. The research approach used in this research is associative. The sample used by purposive sampling is 12 companies for the years 2016-2019. Data analysis techniques used are descriptive statistics, multiple linear regression test panel data model, hypothesis testing (t-test and F-test) and the coefficient of determination test. The results of this study indicate that partially the size of the debt tax shield has an effect on the capital structure and the effective tax rate has no effect on the capital structure. Then Debt tax share and Effective tax rate simultaneously affect the capital structure. Thus, decision makers can use these ratios as a tool of consideration in making policies in the corporate tax system.